Proceedings of the 1st International Conference on Industrial Networks and Intelligent Systems 2015
DOI: 10.4108/icst.iniscom.2015.258274
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Elephant Flow Detection with Cost-Sensitive in SDN

Abstract: Abstract-The software defined networking (SDN) allows separating control and data plane, which provides better network management and higher utilization for data center network. Among these topical applications in SDN, such as traffic engineering, QoS and network management, there is significant interest on classifying the flows and predict future traffic. Classification plays an important role in SDN, especially for elephant flow detection. However, how to efficiently detect all kinds of flows with low cost s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 17 publications
(19 reference statements)
0
29
0
Order By: Relevance
“…Figure 7 shows the accuracy of our purposed classification for various training sizes. We observed that our EF detection method on the controller-side achieves a higher accuracy than the existing EEFD method [21] by up to 0.7%, and the classification-based EDMAR [22] by up to 0.5%.…”
Section: ) Classification Accuracymentioning
confidence: 80%
See 2 more Smart Citations
“…Figure 7 shows the accuracy of our purposed classification for various training sizes. We observed that our EF detection method on the controller-side achieves a higher accuracy than the existing EEFD method [21] by up to 0.7%, and the classification-based EDMAR [22] by up to 0.5%.…”
Section: ) Classification Accuracymentioning
confidence: 80%
“…A real-time EF detection system was proposed in [21]. The proposed method is comprised of two stages according to the statistical thresholding of the flow stream features.…”
Section: ) Switch Based Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pouper et al [21] propose the use of neural networks, Gaussian mixture models and Gaussian process regression for the prediction of the flow size. Xiao et al [22] use C4.5 decision trees and Viljoen et al [23] are using a neural network to classify flows into mice and elephant. Chao et al [24] uses a 2-stage detection scheme with C4.5 trees as a first stage and stream mining with Hoeffding trees in the second stage.…”
Section: B Elephant Flow Detectionmentioning
confidence: 99%
“…According to Benson et al, for interdata center communication, 80% of the flows are smaller than 10 KB in size, and most of the bytes are in the top 10% of the flows that we called elephant flows. Elephant Flow Detection and CheetahFlow both predict the elephant flows and reroute them to other paths to prevent congestion. In addition, CheetahFlow also utilizes the support vector machine (SVM) to construct frequent communication pairs and pre‐establish their flow entries into switches to decrease provisioning latency.…”
Section: Introductionmentioning
confidence: 99%